<span>Simplifying
w + -11 = 1.3
Reorder the terms:
-11 + w = 1.3
Solving
-11 + w = 1.3
Solving for variable 'w'.
Move all terms containing w to the left, all other terms to the right.
Add '11' to each side of the equation.
-11 + 11 + w = 1.3 + 11
Combine like terms: -11 + 11 = 0
0 + w = 1.3 + 11
w = 1.3 + 11
Combine like terms: 1.3 + 11 = 12.3
w = 12.3
Simplifying
w = 12.3 <--- (Answer)
Happy studying ^-^</span>
Answer:
2 11/12
Step-by-step explanation:
3/4 + 2 1/6
Add the fractions.
35/12
= 2 11/12
Do you want square root? And If so then here is the answer:Rewrite <span><span>√37</span>37</span> as <span><span>√3√7</span>37</span>.<span><span>√3√7</span>37</span>Multiply <span><span>√3√7</span>37</span> by <span><span>√7√7</span>77</span>.<span><span><span>√3√7</span><span>√7√7</span></span><span>3777</span></span>Simplify. And in the end of, this I put the decimals.√<span><span>217</span><span>217</span></span>The result can be shown in both exact and decimal forms.Exact Form:<span><span><span>√21</span>7</span></span>Decimal Form:<span>0.65465367<span>… not sure this answer.
</span></span>
Answer: 25 or 30-60
Step-by-step explanation:
Vote me for branliest Have a great day or night everyone!!!